2019
DOI: 10.1016/j.ijid.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete functional T-cell reconstitution in immunological non-responders at one year after initiation of antiretroviral therapy possibly predisposes them to infectious diseases

Abstract: Background: Immunological non-responders (INR) represent a unique category of HIV-infected patients on antiretroviral therapy. These patients have suppressed viremia but a suboptimal increase in CD4 cell count, which might have opposing effects on functional immune reconstitution. Hence, the extent of immune reconstitution in INR patients was investigated in order to determine their susceptibility to opportunistic infections. Methods: Twenty-three INR patients (CD4 increase <50 cells/mm 3 , viral load <40 copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Immune activation markers are likely to be influenced by immune status of the patients and may vary depending on the extent of immunosuppression in these patients. Additionally, presence of other co-existing had also shown that patients with immunologic nonresponse were likely to have frequent co-existing infections [20] possibly impacting levels of immune activation markers. Receiver operating characteristic (ROC) curve for Galectin-9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Immune activation markers are likely to be influenced by immune status of the patients and may vary depending on the extent of immunosuppression in these patients. Additionally, presence of other co-existing had also shown that patients with immunologic nonresponse were likely to have frequent co-existing infections [20] possibly impacting levels of immune activation markers. Receiver operating characteristic (ROC) curve for Galectin-9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the CD4 + T-cell count > 100 cells/µl from baseline at 1 year after ART initiation, with plasma HIV RNA < 40 copies/ml. 47 Total CD4 + T-cell count < 270 cells/µl at 2 years after ART initiation, with an undetectable plasma VL.…”
Section: Definition Of "Immunological Nonresponder" Definition Of "Immentioning
confidence: 98%
“…These studies suggest that in the case of lymphopenia, ongoing thymopoies may contribute to immune recovery in adult HIV‐1‐infected individuals. It has been shown that the frequency of CD4 + RTE cells, the numbers of sj‐TRECs and the sj/β‐TREC ratios are markedly lower in INRs than in IRs and healthy individuals, indicating that lower thymic output is the main cause of incomplete immune recovery in these patients . Furthermore, Menkova‐Garnier et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are categorized as non-immune responders (NIR). [58] In a pilot open labeled clinical trial, Zhang et al, administered 7 NIR patients with three doses of umbilical cord-MSCs and 6 NIRs served as controls. The results revealed an increase in circulating naive and central memory CD4 T-cell counts along with HIV-1-specific IFN-γ and IL-2 generation.…”
Section: Introductionmentioning
confidence: 99%